Quality of life in children without parents placed in foster families - Georgievska, Sofija; Trajkov, Ivan (Ревија за социјална политика/Journal of Social Policy, 2017)
Republic of Macedonia establishes the system of social protection and enables its functioning, by providing conditions and measures for social - protective activities. By promoting the process of deinstitutionalization, the idea of preventing the institutionalization of children with moderate and severe mental disability is imposed, as well as the need to initiate activities to support families, including taking responsibility for improving the quality of life of children while keeping them in a home environment. Carers who agree to care for a child within the family, will need to provide love, warmth and care for his health, education, as well as provide stability and security. Within this research, we questioned 47 children who receive care outside the institutions (SOS foster families and other foster families) and 38 children placed in institutional care (11 Oktomvri). The quality of life was assessed with the questionnaire for the quality of life – PedsQLTM. Results shoed that males aged 5-12 years within the system of social protection evaluate their quality of life as lowest, children and adolescents from institutions evaluate their quality of life lower compared with children and adolescents in foster families and the general population. Also, children and adolescents from institutions have the lowest score in emotional functions as a domain of quality of life, while the children and adolescents of the foster families have a minimum quality of life in the area of physical functioning.
Keywords: children without parental care; care providers; social protection; quality of life